How did an international football competition influence the number of 999 calls a national ambulance service had to respond to? A retrospective study - Reem Bassam Tluli (18505131) (2024)
Background Mega sporting events attract many international fans, which may significantly impact the population size. Ambulance Services have finite resources to meet daily performance targets. The inability to cope with increased call volumes can negatively impact service performance and patient care. This study investigates how the FIFA World Cup (WC) Qatar 2022TM affected regular emergency ambulance call volumes, by comparing the number of ambulance dispatches during the football with previous call volume data for the same period in the previous three years. Methods Qatar’s 999 call volume data for the months of November and December 2019 to 2022 was compared with respect to the population size. This excluded patient encounters that occurred at pre-hospital mobile clinics of FIFA World Cup venues and with paramedic foot patrols. Results The combined 999 call volume for November and December of each of the years of interest are reported in Table 1 alongside the average population size over the 2 months. The most significant population growth occurred in November and December 2022, with +8.01% rise compared to 2021. Regarding 999 calls, the greatest number of calls were during the competition months, with 48,645 calls. It was similar to what was anticipated based on a logistics regression analysis using previous years’ population size and call volume (Figure 1). Conclusion Hosting countries such events must be well-prepared with resources, trained medical staff, and improved healthcare coordination to ensure everyone’s safety. The WC in Qatar had a noticeable impact on the country's population but a less than expected impact on emergency ambulance call volumes. This can be explained by the accessibility of clinics and paramedic foot patrols at all FIFA related venues who could deal with many patient complaints, hence reducing the need for calling an ambulance and visiting hospital emergency departments.